Pengaruh Model Pembelajaran Problem Based Learning Terhadap Minat Belajar Matematika Siswa Kelas VIII Pondok Pesantren Al-Irsyad TI Bulaan Kamba - Silvi Yarda Rahmi; Haida Fitri; Aniswita Aniswita; Pipit Firmanti (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is motivated by the problems in class VIII of Al-Irsyad TI Bulaan Kamba Islamic Boarding School that the learning process is still centered on the teacher, lack of student response to mathematics learning, lack of student courage to ask the teacher, students still think mathematics is difficult and scary, lack of interest in learning mathematics, and students are less enthusiastic when participating in mathematics learning. One alternative learning that can be done to overcome these problems is to apply the Problem Based Learning learning model. This study aims to determine the effect of the Problem Based Learning learning model on the interest in learning mathematics of class VIII students of Al Irsyad TI Bulaan Kamba Islamic Boarding School. The hypothesis in this study is